Translating genetic risk factors for prostate cancer to the clinic: 2013 and beyond. (July 2014) - Mikropoulos, Christos; Goh, Chee; Leongamornlert, Daniel; Kote-Jarai, Zsofia; Eeles, Rosalind
ABSTRACT: : Prostate cancer (PrCa) is the most commonly diagnosed cancer in the male UK population, with over 40, 000 new cases per year. PrCa has a complex, polygenic predisposition, due to rare variants such as BRCA and common variants such as single nucleotide polymorphisms (SNPs). With the introduction of genome-wide association studies, 78 susceptibility loci (SNPs) associated with PrCa risk have been identified. Genetic profiling could risk-stratify a population, leading to the discovery of a higher proportion of clinically significant disease and a reduction in the morbidity related to age-based prostate-specific antigen screening. Based on the combined risk of the 78 SNPs identified so far, the top 1% of the risk distribution has a 4.7-times higher risk of developing PrCa compared with the average of the general population.